Translation of the Fear of COVID-19 Scale into French-Canadian and English-Canadian and Validation in the Nursing Staff of Quebec - Gélinas, Céline; Maheu, Christine; Lavoie-Tremblay, Mélanie; Richard-Lalonde, Mélissa; Gallani, Maria; Gosselin, Émilie; Hébert, Maude; Tchouaket Nguemeleu, Eric; Côté, José (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2021)
Introduction: During the COVID-19 pandemic, Quebec has been one of the most affected provinces in Canada. Rising fear of COVID-19 is inevitable among healthcare workers, and a new scale was developed to measure this type of fear, the Fear of COVID-19 Scale (FCV-19S). Aims: To translate the FCV-19S into French-Canadian and English-Canadian, and to validate both versions in the nursing staff from Quebec. Methods: A cross-sectional online survey was sent to approximately 15 000 nursing staff including nurses and licensed practical nurses among those who had consented to their respective Order to be contacted for research. The forward-backward method was used to translate the FCV-19S into French-Canadian and English-Canadian. Both versions along with stress and work-related questionnaires, were used to establish validity. Results: A total of 1708 nursing staff, with a majority of women, completed the survey (1517 and 191 completed the French-Canadian and English-Canadian versions). A unidimensional scale was confirmed for both versions with Cronbach alphas of 0.90 and 0.88. Discriminative values showed higher fear levels in women, and in generation X (40-56 years old). Higher fear levels were also found in nursing staff working in long-term care facilities, provided care to COVID-19 patients who died, and those who felt less prepared to provide safe care. Convergent associations were found between fear levels, stress, work satisfaction, and turnover intention. Discussion and conclusion: A rigorous approach was used to translate the fear of COVID-19 scale into French-Canadian and English-Canadian. Both Canadian versions of the FCV-19S supported a valid unidimensional scale in Quebec nursing staff.